황련청심음(黃連淸心飮)의 항산화 및 AChE 억제 효과에 관한 연구 - 김헌일; Hun Il Kim; 유종호; Jong Ho Kim; 이상택; Sang Taek Lee; 한윤승; Seung Yun Han; 김근우; Geun Woo Kim; 구병수; Byung Soo Koo (동의신경정신과학회지, 2006)
Objective: An water extract of the Hwang-Ryun-Chung-Sim-Um (HRC) was assessed to determine the mechanisms of its antioxidant activity. In addition, the HRC was examined in vitro for the inhibitory effect on the acetylcholinesterse (AChE). Methods: The HRC exhibited a concentration-treatment; scavenging α,α-diphenyl-β-picrylhydrazyl (DPPH) radical, linoleic acid oxidation in a thiocyanate assay system, hydroxyl radical-induced DNA nicking. We investigated mRNA levels such as catalase activity, superoxide-dismutase and glutathione peroxidase. The water extract of HRC showed inhibitory effect on AChE activity. Result: The HRC extract showed dose-dependent free radical scavenging activity, including DPPH radicals and hydroxyl radicals, using different system. The HRC was also found to be effective in protecting plasmid DNA against the strand breakage induced by Hydroxyl radicals in Fenton`s reaction mixture. Futhermore, catalase mRNA expression levels increased, but SOD1 and MnSOD was not expressed. HRC in a various concentration-dependent decreased AChE mRNA levels and inhibitory effect showed AChE. Conclusion: According to the above results, it is supposed that HRC is applicable to the Dementia-type of Alzheimer clinically.